Characterization of Chemical Treated Eichhornia Crassipes Fibers and Its Composites - Basanta Kumar Palai; Saroj Kumar Sarangi (Journal of Natural Fibers, 2022)
Natural fiber composites are preferred over synthetic fiber composites nowadays because of their various attractive features like biodegradability, easy processing and light-weight. In order to improve the strength of the natural fibers to be used for composite preparation, they are subjected to suitable chemical treatments. In the present work, natural fiber composites made up of untreated and treated Eichhornia crassipes fibers (ECFs) have been tested for their mechanical properties. The raw ECFs have been optimally treated with 5% NaOH solution, and then, the optimally NaoH treated ECFs have been individually treated with benzoyl peroxide solution, potassium permanganate solution and stearic acid solution. The five ECF samples have been characterized for predicting their physical, chemical, crystalline and thermal stability properties. Composite specimens have been prepared with all the five ECF samples under different fiber loading, viz., 5 wt.%, 10 wt.%, 15 wt.%, 20 wt.% and 25 wt.%. From the test results, it has been observed that the stearic acid solution treated ECFs with 20 wt. % fiber exhibits better tensile strength (46.97 MPa), flexural strength (61.863 MPa) and impact strength (86.74 N/m).